Detection of SARS-CoV-2 in Nasal Swabs: comparison with Nasopharyngeal Swabs - Hyun Ah Kim; Miri Hyun; Ji Yeon Lee; Sunggyun Park; Namhee Ryoo; Yong Shik Kwon; Jae Seok Park; Jin Young Kim; Jae Cheon Jeon; Kyong Ran Peck (Journal of Infection in Developing Countries)
.